A new restriction fragment length polymorphism at the DXS101 locus allows carrier detection in a family with X linked agammaglobulinaemia. Issue 6 (June 1993) - Sweatman, A; Lovering, R; Middleton-Price, H; Jones, A; Morgan, G; Levinsky, R; Kinnon, C
Abstract : The gene responsible for X linked agammaglobulinaemia (XLA) lies in Xq22 and has recently been identified as atk. DXS101 is a polymorphic locus which is closely linked to the disease locus. In this report we describe the identification, by pulsed field gel electrophoresis, of a new polymorphism at the DXS101 locus with a predicted heterozygosity of 4.9%. Despite this low value, we show how this polymorphism has been important in carrier status determination in a family with XLA where assessment was not possible by other means.